2018
DOI: 10.21614/chirurgia.113.2.202
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Approach in Benign and Malignant Esophageal Tumors; A Preliminary Seven Case Series

Abstract: Our experience is limited and we cannot conclude for the long term benefits of robotic surgery for esophageal tumors. In our experience the early outcomes were better then using classic open approach, but similar with the cases performed by thoracoscopic approach. We have noticed significant advantages of robotic surgery in relation of lymph node retrieval, leiomyoma dissection safe from esophageal mucosa and suturing. Ergonomics for the surgeon was incomparable better then with the thoracoscopic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Robotic surgery could be another highly sophisticated treatment option in some referral centres. The procedure is safe, provides comparable outcomes to thoracoscopy and offers better ergonomics to well-trained surgeons, but only in very few, highly selected patients [30,31]. Cerfolio et al reported four successful leiomyoma resections using a robotic platform, demonstrating the biggest series worldwide in this area [32].…”
Section: Discussionmentioning
confidence: 99%
“…Robotic surgery could be another highly sophisticated treatment option in some referral centres. The procedure is safe, provides comparable outcomes to thoracoscopy and offers better ergonomics to well-trained surgeons, but only in very few, highly selected patients [30,31]. Cerfolio et al reported four successful leiomyoma resections using a robotic platform, demonstrating the biggest series worldwide in this area [32].…”
Section: Discussionmentioning
confidence: 99%
“…5,6 These tumours usually at the time of diagnosis measure less than 5 cm but if they are larger than 10 cm, they are called giant leiomyomas and may be single or multiple. 7,8 Most patients with oesophageal leiomyomas are detected incidentally, however when they attain bigger size, they can cause symptoms like dysphagia, regurgitation, weight loss and chest pain. 10,15 Factors such as tumour size of more than 4 to 5 cm, presence of symptoms, location of the tumour, mucosal ulcerations and if malignancy cannot be ruled out, are considered as indications for surgical intervention whereas asymptomatic lesions and lesions < 4 to 5 cm in size can be managed conservatively with regular follow-up UGIE and contrast studies.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Tumours larger than 10 cm are called Giant Leiomyomas and may be single or multiple. 7,8 Leiomyomas are often misdiagnosed as mediastinal mass, oesophageal cancer and gastrointestinal stromal tumour (GIST). Preoperative diagnosis is aided with imaging studies like computed tomography (CT), upper gastrointestinal endoscopy (UGIE), and endoscopic ultrasound (EUS).…”
Section: Introductionmentioning
confidence: 99%
“…Although esophageal cancer is less common than other cancers, a wide range of lesions of other areas related to the neck, breast, and belly [37] characterizes it. The principles of surgical treatment include a decrease in surgical injury, contributing to the restoration of patients, and improving treatment safety based on the premise of complete resection of the tumor and adequate lymph dissection [38].…”
Section: Esophageal Carcinomamentioning
confidence: 99%